Carbon dioxide capture using aqueous monoethanolamine and biodiesel production from chlorella ellipsoidea, spirulina and nannochloropsis sp - De Venecia, Mark Vincent (Animo Repository, 2016)
Gas absorption for carbon dioxide capture using aqueous monoethanolamine coupled with biofixation using Chlorella ellipsoidea, Nannochloropsis sp and Spirulina in a flask flat plate photobioreactor system was proposed to evaluate the feasibility of the system as an alternative to achieve sustainable development without the utilization of non-renewable energy sources. The produced biomass was also evaluated if it can be used as feedstock for biodiesel production by subjecting it to FAME analysis. CO2 absorption using MEA solution was optimized utilizing the Taguchi orthogonal array design with factors being MEA and CO2 concentration, Temperature of entering MEA solution and Liquid flow rate to yield a high absorption capacity for the absorption capacity for the absorption column. The optimum conditions were found to be 1.5M MEA concentration, 8% CO2, 25ï‚°C temperature of MEA solution and 1.25 L/min liquid flow rate which yielded 0.3312{u1D45A}{u1D45C}{u1D459}{u1D452}{u1D460} {u1D436}{u1D442}2 {u1D43F}.Optimum product obtained from the CO2 optimization was used as feed in the photobioreactor system for CO2biofixation. The growth of Chlorella ellipsoidea, Nannochloropsis sp and Spirulina in the MEA-CO2 medium was determined using optical density and dry weight of the biomass. Results showed that algae should be harvested on the 3rd day, which was the stationary phase of all the algae species, to avoid the nutrient release into the medium caused by the death of the algae. All algae species displayed potential growth in MEA-CO2 medium. MEA and CO2 concentration was monitored in the photobioreactor to determine whether the algae consume the CO2 and nitrogen present in the solution. Results showed that all the species consumed the dissolved CO2 up until the stationary phase. Chlorella ellipsoidea and Nannochloropsis sp had decreasing MEA concentrations during its life cycle however the MEA in the Spirulina photobioreactor remained constant up until its death phase. All the algae species were subjected to FAME analysis to profile their fatty acid content to determine their potential as biodiesel feedstock.